Development and Applications of Portable Biosensors. (August 2015) - Srinivasan, Balaji; Tung, Steve
The significance of microfluidics-based and microelectromechanical systems–based biosensors has been widely acknowledged, and many reviews have explored their potential applications in clinical diagnostics, personalized medicine, global health, drug discovery, food safety, and forensics. Because health care costs are increasing, there is an increasing need to remotely monitor the health condition of patients by point-of-care-testing. The demand for biosensors for detection of biological warfare agents has increased, and research is focused on ways of producing small portable devices that would allow fast, accurate, and on-site detection. In the past decade, the demand for rapid and accurate on-site detection of plant disease diagnosis has increased due to emerging pathogens with resistance to pesticides, increased human mobility, and regulations limiting the application of toxic chemicals to prevent spread of diseases. The portability of biosensors for on-site diagnosis is limited due to various issues, including sample preparation techniques, fluid-handling techniques, the limited lifetime of biological reagents, device packaging, integrating electronics for data collection/analysis, and the requirement of external accessories and power. Many microfluidic, electronic, and biological design strategies, such as handling liquids in biosensors without pumps/valves, the application of droplet-based microfluidics, paper-based microfluidic devices, and wireless networking capabilities for data transmission, are being explored.